Symposium labor preterm. Introduction - Ciudad Reynaud, Antonio (2015)
This symposium is about one of the biggest problems in obstetrics, to date, despite the advance of technology, knowledge and even social development, it does not adequately reduced its prevalence. Preterm birth is a major cause of perinatal death and, therefore, is one of the gravitating in infant mortality factors.